2006
DOI: 10.1038/nature05288
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the FOXO1–PGC-1α connection

Abstract: Increased expression of the gene encoding the enzyme glucose-6-phosphatase (G6Pase) contributes to the increased production of glucose by the liver that occurs in individuals with diabetes. Puigserver et al. show that the transcription factor FOXO1 and the transcriptional co-activator PGC-1alpha act synergistically to stimulate the expression of genes in the gluconeogenesis pathway and propose that PGC-1alpha acts, in part, directly through FOXO1. Here we show that FOXO1 is neither required nor sufficient for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 7 publications
3
45
0
Order By: Relevance
“…More recently, Matsumoto and colleagues [45] demonstrated in primary hepatocytes lacking FOXO1 that the induction of G6PC expression by PGC-1α was markedly reduced. This is consistent with the synergistic interaction between FOXO1 and PGC-1α seen in both H4IIE cells [41] and immortalised mouse hepatocytes [40]. However, while the effect of PGC-1α on G6pc expression was markedly reduced in primary hepatocytes lacking FOXO1, a~20-fold induction remained [45].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…More recently, Matsumoto and colleagues [45] demonstrated in primary hepatocytes lacking FOXO1 that the induction of G6PC expression by PGC-1α was markedly reduced. This is consistent with the synergistic interaction between FOXO1 and PGC-1α seen in both H4IIE cells [41] and immortalised mouse hepatocytes [40]. However, while the effect of PGC-1α on G6pc expression was markedly reduced in primary hepatocytes lacking FOXO1, a~20-fold induction remained [45].…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, the ability of PGC-1α to stimulate G6pc expression in hepatocytes derived from mice lacking HNF-4α is completely lost [20]. The results of Matsumoto and colleagues [45] are therefore consistent with our model, in which PGC-1α stimulates G6PC-luciferase fusion gene expression through HNF-4α, with the binding of FOXO1 to the G6PC promoter being neither required nor sufficient for this induction, although it does act synergistically to enhance the response [41]. Published reports suggest that this model is also consistent with the mechanism of action of PGC-1α on PEPCK expression.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…(Puigserver et al 1998;Herzig et al 2001;Lin et al 2002;Puigserver et al 2003;Rhee et al 2003;Arany et al 2005;St-Pierre et al 2006;Handschin et al 2007). While named for its interaction with PPARγ, many of these PGC-1-dependent adaptations appear to be largely dependent on ERRs and other metabolic transcription factors that are independent of PPAR/RXR Rhee et al 2003;Schilling et al 2006;Alaynick et al 2007;Huss et al 2007;Villena et al 2007). …”
Section: Pgc-1αmentioning
confidence: 99%
“…The authors propose a model in which the direct interaction of PGC-1a with Foxo1 leads to increased binding of Foxo1 to the promoter of G6Pase (Puigserver et al, 2003). However, a recent report has suggested that the synergism between PGC1a and Foxo1 is not the consequence of a direct Foxo1 PGC-1a interaction, but rather results from the presence of both Foxo1 and nuclear receptor-binding sites in the G6Pase promoter (Schilling et al, 2006). In this experimental setup, mutation of FOXO-binding sites did not decrease the ability of PGC1a to increase G6Pase expression, whereas mutating the nuclear receptor-binding site did (Schilling et al, 2006).…”
Section: Regulation Of Glucose and Fatty Acid Metabolism By Foxo-intementioning
confidence: 99%